Factors influencing intercourse frequency among the young and middle-aged men - Peng, Jingxuan; Peng, Emin (Zhong nan da xue xue bao. Journal of Central South University. Yi xue ban, 2022)
At present, there are few studies on the sexual activity of young and middle-aged men in China. This study aims to explore the factors that affect the frequency of intercourse among young and middle-aged men in China. Data for 923 men aged 20-60 years were collected in the Health Management Center, Third Xiangya Hospital, Central South University from January 2019 to March 2019, and a questionnaire survey (including basic conditions and sexual function-related scales) was carried out in the subjects. Finally, the data were analyzed by multivariate logistic regression analysis. The age ( <0.01), number of children ( <0.01), total cholesterol ( <0.05), low-density lipoprotein ( <0.05), erectile function ( <0.01) and premature ejaculation ( <0.05) was significantly correlated with the frequency of intercourse in the young and middle-aged men in China. The sexual frequency in the middle-young men in China is closely related to factors such as age, number of children, total cholesterol, low-density lipoprotein, and sex function.